OPTIMIZING ACUTE LYMPHOBLASTIC LEUKEMIA PATIENT LENGTH OF STAY (LOS) IN KARIADI HOSPITAL: A QUASIEXPERIMENTAL STUDY - Kusumawati, Ninung Rose Diana; Trisnantoro, Laksono; Basir, Slamet; Prabawa, Liauw Jaya; Risanty, Sofie Astri (Jurnal Manajemen Kesehatan Indonesia, 2025)
Prolonged length of stay (LOS) in acute lymphoblastic leukemia (ALL) patients contributes to overcrowding, increased healthcare costs, and reduced bed availability, especially in Indonesian referral hospitals. Although structured discharge planning and clinical pathway integration have shown potential in reducing LOS, their application in Indonesian cancer centers remains limited. This study aimed to find the strategy needed to reduce LOS among ALL patients at Dr. Kariadi Hospital. A sequential exploratory mixed-methods design was employed. In the qualitative phase, two rounds of focus group discussions (n = 12 healthcare professionals) identified and prioritized causes of prolonged LOS using a fishbone diagram and Urgency–Seriousness–Growth (USG) scoring. The quantitative phase evaluated all medical records (preintervention: January–June 2024; post-intervention: July– December 2024) to measure impact. The absence of structured discharge planning and clinical pathway integration into the electronic medical record (EMR) were identified as key issues. Based on these findings, a mandatory discharge planning and clinical pathway entry was introduced for all suspected ALL admissions. The intervention reduced average LOS from 10.14 days to 3.13 days, showing a 7.01-day reduction. These results align with international evidence supporting discharge planning and pathway integration to improve care efficiency. Integrating discharge planning and clinical pathways into the initial inpatient assessment significantly reduced LOS among ALL patients. This low-cost, EMR-based strategy holds promise for wider adoption in resource-constrained hospital settings across Indonesia.